Prognostic and Clinicopathological Significance of the Systemic Immune-Inflammation Index in Patients With Renal Cell Carcinoma: A Meta-Analysis - Jin, Mingyu; Yuan, Shaoying; Yuan, Yiming; Yi, Luqi (Frontiers in Oncology, 2021)
Background: The systemic immune-inflammation index (SII) is a hematological parameter based on neutrophil, platelet, and lymphocyte counts. Studies that have investigated the prognostic value of SII in patients with renal cell carcinoma (RCC) have reported controversial results. In this study, we systematically investigated the prognostic value of SII in patients with RCC. Methods: We systematically searched English articles in the PubMed, Embase, Web of Science, and Cochrane Library databases up to October 2021. Hazard ratios (HRs) and odds ratios (ORs) with 95% confidence intervals (CIs) were used to obtain pooled results. Results: The meta-analysis included 10 studies that enrolled 3,180 patients. A high SII was associated with poor overall survival (HR 1.75, 95% CI 1.33–2.30, p<0.001) in patients with RCC. However, a high SII was not shown to be a significant prognostic factor for progression-free survival/disease-free survival (HR 1.22, 95% CI 0.84–1.76, p=0.293) or poor cancer-specific survival (HR 1.46, 95% CI 0.68–3.12, p=0.332) in patients with RCC. A high SII was correlated with male sex (OR 1.51, 95% CI 1.11–2.04, p=0.008), Fuhrman grade G3–G4 (OR 1.80, 95% CI 1.08–3.00, p=0.024), and poor risk based on the International Metastatic Renal Cell Carcinoma Database Consortium criteria (OR 19.12, 95% CI 9.13–40.06, p<0.001). Conclusion: A high SII was independently associated with poor survival outcomes in patients with RCC. Additionally, an elevated SII indicated more aggressive disease. The SII may serve as a useful cost-effective prognostic indicator in patients with RCC.